PHYSICAL EDUCATION, HISTORICAL-CRITICAL PEDAGOGY AND SCHOOL EDUCATION (Fiep Bulletin - online, 2016)
The current paper aims to conduct a brief theoretical approach between Physical Education, historical-critical pedagogy and school education in order to contribute to the formation of the working class, giving importance to human emancipation and overcoming a society of classes. This way, a literature review will be made, and it will encompass the historical-critical pedagogy with the explanation of the theoretical and methodological foundations and the articulation of some concepts of critical-surpassing methodology of Physical Education, so that it is possible to envisage a teaching practice of this discipline in school beyond common sense and mere technical reproduction of movement. In other words, this study aims to seek an alternative for the education of workers, from the School Physical Education contribution to the formation of historical individuals, able to understand the reality and its multiple determinations.
Keywords: School Physical Education; historical-critical pedagogy; human formation